Childhood heart problems, adulthood emotional stability, and sex associated with self-report heart conditions in adulthood. (March 2021) - Cheng, Helen; Montgomery, Scott; Green, Andy; Furnham, Adrian
The present study investigated biomedical, social, and psychological factors associated with self-reported heart conditions in adulthood in a British cohort. In total, 5697 (50.7% males) participants with data on parental socioeconomic status, childhood cognitive ability, childhood heart problems, educational qualifications, current occupational levels, adulthood personality traits, and the prevalence of self-reported heart conditions in adulthood were included in the study. The prevalence of self-reported heart conditions measured at age 54 years was the outcome variable. Hierarchical logistic regression analysis showed that childhood heart problems identified by physicians (OR = 3.47:1.74–6.92, p  < 0.001) and trait emotional stability (OR = 0.83:0.75–0.93, p  < 0.001) were the significant and independent predictors of self-reported heart conditions in adulthood. There were also significant sex effects on the prevalence of the outcome variable (OR = 0.53:0.42–0.63, p  < 0.001). Both a biomedical and a psychological factor were significantly associated with self-reported heart conditions in adulthood.